EFFICACY AND SAFETY OF HERBAL MEDICINES IN ASIA - Baihaqi, Achmad Al; Levita, Jutti (Faculty of Mathematic and Natural Science, Garut University, 2021)
Herbal medicine (HM) is a part of future alternative health care. According to the World Health Organization (WHO), almost 70-80% of the population of developing countries rely on HM as an immediate need for health services, one of which is the Asian region. With the high trend of a healthy lifestyle using natural ingredients, drug safety must be a significant concern. This review article aims to provide information on studying the toxicity of Asian herbal plants to hepatotoxic and nephrotoxic activities. The research method was conducted by searching using the keywords â€œHerbal Medicine(HM),â€ â€œEfficacy,â€ â€œNephrotoxicity,â€ â€œHepatotoxicity,â€ â€œAsia,â€ â€œextractâ€ on the Google site and Google Scholar. The primary data sources used consisted of national journals, international journals, and the WHO website. Articles were screened using the inclusion criteria of Indonesian and English journals published in the last ten years. Of the toxicity study articles discussing 10 herbs-induced liver injury (HILI) and 10 drug-induced liver injury (DILI) that we reviewed, it is known that the dose consumed has a more significant effect on the incidence of hepatotoxicity and nephrotoxicity than the duration of administration with low doses slot deposit 5000. However, the period of administration with high doses has a significant relationship with liver and kidney damage. Therefore, disseminating safety studies to the public is very important to maximize drug efficacy and avoid hepatotoxicity and nephrotoxicity. Keywords: herbal medicine (HM); hepatotoxicity; nephrotoxicity; Asia; safety